A review on fundamentals and strategy of epoxy-resin-based anticorrosive coating materials. Issue 6 (13th April 2021) - Ou, Baoli; Wang, Yuwei; Lu, Yi
ABSTRACT: In the field of anticorrosion, epoxy resin plays an important role. Therefore, many researchers have reported the strategy, manufacturing technology, and application of epoxy anticorrosive coatings all over the world. In this paper, three basic ideas for improving the anticorrosion performance of epoxy resin anticorrosive materials are summarized, and the current strategies for developing new epoxy resins are classified into seven types. In the end, it is pointed out that with the development of technology, the development direction of anticorrosive coatings should be toward multifunctional coatings and composite materials.